Health Literacy and Urbanicity Among Cancer Patients. Issue 4 (25th March 2013) - Halverson, Julie; Martinez‐Donate, Ana; Trentham‐Dietz, Amy; Walsh, Matthew C.; Strickland, Jeanne Schaaf; Palta, Mari; Smith, Paul D.; Cleary, James
Abstract Purpose Low health literacy is associated with inadequate health care utilization and poor health outcomes, particularly among elderly persons. There is a dearth of research exploring the relationship between health literacy and place of residence (urbanicity). This study examined the association between urbanicity and health literacy, as well as factors related to low health literacy, among cancer patients. Methods A cross‐sectional survey was conducted with a population‐based sample of 1, 841 cancer patients in Wisconsin. Data on sociodemographics, urbanicity, clinical characteristics, insurance status, and health literacy were obtained from the state's cancer registry and participants' answers to a mailed questionnaire. Partially and fully adjusted multivariate logistic regression models were fitted to examine: (1) the association between urbanicity and health literacy and (2) the role of socioeconomic status as a possible mediator of this relationship. Findings Rural cancer patients had a 33% (95% CI: 1.06‐1.67) higher odds of having lower levels of health literacy than their counterparts in more urban areas of Wisconsin. The association between urbanicity and health literacy attenuated after controlling for socioeconomic status. Conclusions Level of urbanicity was significantly related to health literacy. Socioeconomic status fully mediated the relationship between urbanicity and health literacy. These results call for policies and interventions to assess and address health literacy barriers among cancer patients in rural areas.